The discourse of inclusive education: challenges for the deaf in learning Portuguese - Grillo, Jocimara Paiva; Guerra, Vania Maria Lescano (The ESPecialist, 2024)
This article presents some challenges that deaf people face in relation to learning the Portuguese language in the written modality. Based methodologically on Foucauldian studies, this study presents the state of the art on the teaching of Portuguese as an additional language for deaf people. The text shows the importance of Libras (Brazilian Sign Language) for the deaf person and, therefore, the challenges in teaching the Portuguese language as an additional language to the deaf. Thus, in the light of transdisciplinarity, we bring theories based on a discursive view and on the perspective of decolonial studies in the search to understand the identity representations of the deaf. To this end, this article problematizes excerpts from the text entitled "Open Letter from Deaf Doctors", addressed to the then Minister of Education Mercadante, dated June 8, 2012, published on the web. We understand that additional language teaching for deaf students needs garantir um processo de ensino e aprendizagem predominante em sua formação acadêmica . Alguns resultados indicam que a educação das crianças surdas é um problema educacional , assim como a educação das classes populares , da educação rural , dos meninos de rua , dos presos , dos presos especiais , dos indígenas , dos analfabetos , ou seja , dos grupos que estão na periferia social . .